Genome-Wide Association Study of Motor Coordination - Mountford, Hayley S.; Hill, Amanda; Barnett, Anna L.; Newbury, Dianne F. (Frontiers in Human Neuroscience, 2021)
The ability to finely control our movement is key to the achieving many of the educational milestones and life-skills we develop throughout our lives. Despite the centrality of coordination to our early development, there is a vast gap in our understanding of the underlying biology. Like most complex traits, both genetics and environment influence motor coordination, however, the specific genes, early environmental risk factors and molecular pathways are unknown. Previous studies have shown that about 5% of school-age children experience unexplained difficulties with motor coordination. These children are said to have Developmental Coordination Disorder (DCD). For children with DCD, these motor coordination difficulties significantly impact their everyday life and learning. DCD is associated with poorer academic achievement, reduced quality of life, it can constrain career opportunities and increase the risk of mental health issues in adulthood. Despite the high prevalence of coordination difficulties, many children remain undiagnosed by healthcare professionals. Compounding under-diagnosis in the clinic, research into the etiology of DCD is severely underrepresented in the literature. Here we present the first genome-wide association study (GWAS) to examine the genetic basis of early motor coordination in the context of motor difficulties. Using data from the Avon Longitudinal Study of Parents and Children (ALSPAC) we generate a derived measure of motor coordination from four components of the Movement Assessment Battery for Children (MABC), providing an overall measure of coordination across the full range of ability. We perform the first genome-wide association analysis focused on motor coordination (N=4542). No single nucleotide polymorphisms (SNPs) met the threshold for genome-wide significance however 59 SNPs showed suggestive associations. Three regions contained multiple suggestively associated SNP, within five preliminary candidate genes: IQSEC1, LRCC1, SYNJ2B2, ADAM20 and ADAM21. Association to the gene IQSEC1 suggests a potential link to axon guidance and dendritic projection processes as a potential underlying mechanism of motor coordination difficulties. This represents an interesting potential mechanism, and whilst further validation is essential, it generates a direct window into the biology of motor coordination difficulties. This research has identified potential biological drivers of DCD, a first step towards understanding this common, yet neglected neurodevelopmental disorder.